(untitled) (Journal of Population and Development, 2024)
The Paper highlights role of institutions in transition economy. Obviously, the author confirms that Nepal is still in the transition stage where institutional and ethical norms are yet to establish though many political changes occurred in a short span of time. Nepal adopted liberal market economy for speedy economic growth enticed with robust human development. The study attempts to take measure the outcome of new political-economic regime. The objectives of the study are-(i) to assess role of government institutions on economic growth and development in Nepal and (ii) to evaluate institutional performance of Nepal in comparison to other South Asian countries. The secondary data is used for the analysis which captured the period from 2014 to 2022. The data is analysed descriptively. The deductive method is used for the generalization. The study concludes that the average inflation GDP per capita, GDP growth, and doing business are 6.12 percent, 9968.22 USD, 3.36 percent, and 60.11 respectively. Control of corruption performance of Nepal is almost negative throughout the period. Transparency coefficient is medium i.e. 3 out of 6. In the same way, voice and accountability coefficient is also very poor throughout the time Relative analysis suggests that economic variables are sound in Maldives and Bhutan and development variables are sound in Bhutan. In aggregate, Bhutan has done marvellous performance. In both parameters, economic and development, Nepal’s position is not encouraging. It is recommended to the government and political parties that they need to understand the urgency of matter and reform government as well as political institutions at the earliest.